Vaccination Acceptance among Indigenous Community: The Moderating Role of Tribal Leader Endorsement - Denan, Zarina; Othman, Nor Azairiah Fatimah; Abdul Munir, Zarina; Ab Latiff, Dilla Syadia; Zamzuri, Norol Hamiza (Information Management and Business Review, 2023)
Coronavirus disease 2019 cases are showing a downward trend in Malaysia but with active cases still present, the virus remains a persistent public health threat. Amid vaccination at no cost, some of the populace is refusing to get vaccinated. As getting indigenous communities vaccinated are much more difficult due to contextual and cultural difference, this study investigated whether tribal leader endorsement moderates the relationship between attitude and intention towards vaccination. Drawing from a survey of 312 indigenous from various generations of Millennials, Generation X and Generation Z, this study found that endorsement of tribal leaders does not act as a moderating factor in the association between attitude and intention to accept vaccination across generations. This study contributes to understanding whether indigenous communities require cultural-based approaches to support vaccination uptake. This study would be beneficial in supporting initiatives to curb COVID-19 disease and the right to good health among indigenous communities.